A potential photo-protective, antioxidant function for DMSO in marine phytoplankton. - Brandon J McNabb; Philippe D Tortell (PLoS ONE)
The marine compound dimethyl sulfoxide (DMSO) is ubiquitous in the world's surface ocean, constituting one of the largest sources of reduced organic sulfur in seawater. DMSO cycling has been linked to the formation of the climate-active gas dimethyl sulfide (DMS) through a reductive pathway, but the underlying physiological role of DMSO reduction, and the environmental controls on this pathway, remain unresolved. Here we present evidence that DMSO reduction to DMS serves an antioxidant role in phytoplankton through a secondary electron-scavenging pathway that can dissipate excess light-harvested energy, and potentially mitigate the formation of reactive oxygen species (ROS). Results from isotopic tracer experiments demonstrate significant increases in DMSO reduction rates in low-light acclimated natural phytoplankton assemblages exposed to high irradiance. Increased DMSO reduction rates were negatively correlated with non-photochemical quenching, while treatment with the photosynthetic electron transport inhibitor DCMU significantly decreased DMSO reduction, indicating a link to photosynthetically-derived electrons. Our results show that photic stress drives enhanced DMSO reduction in marine phytoplankton, linking DMS production to irradiance and vertical mixing through an electron scavenging mechanism that could serve an antioxidant role.